2016
DOI: 10.3171/2015.3.jns142428
|View full text |Cite
|
Sign up to set email alerts
|

Results of wrist extension reconstruction in C5–8 brachial plexus palsy by transferring the pronator quadratus motor branch to the extensor carpi radialis brevis muscle

Abstract: T radiTionally, it has been accepted that if the C5-7 roots are injured, there will be palsy of shoulder abduction/external rotation, elbow flexion/extension, and thumb and finger extension.1 Although this belief is widely held, it is inconsistent with well-accepted myotome charts for the upper limb.9 For instance, it is accepted that thumb and finger extensors are innervated by the C-7 and C-8 roots; consequently, preservation of thumb and finger span should be observed in C5-7 root injuries. Bertelli and Ghi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
8
0
3
Order By: Relevance
“…8 Several studies have reported spontaneous recovery from the injury for more than 75% of patients after 3 months, 1,13 so in most patients with typical humeral shaft-associated radial nerve injuries, we recommend waiting 4 months, with serial clinical and electrophysiological follow-up prior to exploration. However, for the proximal radial nerve injuries associated with severe stretch mechanisms, as in the series reported herein, 3 we too would recommend exploration by 3-4 months, with intention for nerve grafting.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…8 Several studies have reported spontaneous recovery from the injury for more than 75% of patients after 3 months, 1,13 so in most patients with typical humeral shaft-associated radial nerve injuries, we recommend waiting 4 months, with serial clinical and electrophysiological follow-up prior to exploration. However, for the proximal radial nerve injuries associated with severe stretch mechanisms, as in the series reported herein, 3 we too would recommend exploration by 3-4 months, with intention for nerve grafting.…”
mentioning
confidence: 87%
“…In this article, Bertelli and Ghizoni report on 13 patients with proximal radial nerve injuries, which resulted from high-velocity stretch mechanisms; all patients were injured in motorcycle accidents and many had concomitant musculoskeletal injuries, and several had injuries to other brachial plexus elements. 3 The prevalence of proximal radial nerve injuries is still unknown, unlike the detailed knowledge about the risk of radial nerve palsy due to humeral shaft fractures. The prevalence of radial nerve palsy due to humeral shaft fractures is 11.8%; however, when the shaft length is divided into thirds, only 1.8% of the proximal third fractures are associated with radial palsy, whereas a 15.2% incidence is associated with middle shaft fractures and 23.6% with distal third shaft fractures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…El ramo para el músculo extensor radial corto del carpo (MERCC) ha sido utilizado con frecuencia para restablecer las funciones de antebrazo, muñeca y mano en pacientes con lesiones medulares, del plexo braquial o lesiones que afecten sus ramos terminales (Hsiao et al, 2009;Bertelli et al, 2012Bertelli et al, , 2016.…”
Section: Introductionunclassified
“…El ramo para el MERCC se ha utilizado como nervio donante para el ramo interóseo anterior, flexor largo del pulgar y pronador redondo (Bertelli et al, 2012;Bertelli, 2015), con resultados exitosos en la recuperación principalmente de la flexión de los dedos y oposición de pulgar. Así mismo se han transferido ramos nerviosos hacia el nervio del MERCC, tales como el ramo para el músculo flexor superficial de los dedos, recuperando la función extensora de muñeca en daños por avulsión del plexo braquial a nivel de C5-C6-C7 (Ukrit et al, 2009) y transferencias desde el nervio para el músculo pronador cuadrado, ramo terminal del nervio interóseo anterior en lesiones de plexo braquial C5 -C8 recuperando exitosamente la extension de muñeca (Bertelli et al, 2016).…”
Section: Introductionunclassified